SATU KETIK, RIBUAN AKSI: MENGATALISASI PARTISPIASI OFFLINE PEMUDA INDONESIA DI ERA NEW MEDIA - Gita Nindya Elsitra dan Muhammad Salman Al-Faris (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
It is indeed that the youth activeness in online political participations by new medias are allowed and needs to be increased, but it doesn’t mean that they are allowed to ignore practical political participations in their real life. The youth, as a catalyzer of the nation, have the urgencies of balancing between their online and offline participation. We need to remember that Indonesia is not a country that exist merely in the web and not all of the nation’s problem can be digitalized. Unfortunately, the existence of the youth in the nation’s politics has degraded drastically since the 1998 reformation. Where were the young men who stood in the front line to defend their people and brought terror to the governmental regime in the early 2000s? It’s not an anecdote, but it is a serious problem of recent Indonesian youth, which is hard to tackle. Several things has become the reason of this phenomenon. First one, the new media offers ease to participate in politics. The lack of cost and efforts required has made the youth feel more comfortable to participate via these new medias so they started to ignore participating in offline politics. Second one, new medias cuts the distance between politicians and the society. At this point, the youth may think that the problems will be over by criticising in the comment section of the politicians’ social media accounts, or by writing in their social media timeline, while it actually doesn’t solve any problem. Third one, political-branding media accounts and news portals have appeard a lot more. They often incite useless debates and social media wars. It feels so contradictive seeing our youth comfortably argue in online forums when our fuels are no longer subsidized, our electrcity become more expensive, even while our national general assembly (DPR) is seriously entangled in the e-KTP mega-scandal. By using literature reasearch, the writers compared empirical data from several previous researches and deeply analyzed about the prominent problem. This reasearch results in a new innovation as an alternative solution we can apply by synergizing the role of the youth and the government, which is essential to help balancing the youth’s participations online and offline.